Screening Program for Urinary Tract Infection of Prepubertal Children at Al Nasiriya City Primary Schools - hussien, adil; Abu Raghif, leila (Iraqi National Journal of Nursing Specialties, 2016)
Objective(s): The study aims Finding relationship between UTI and demographic variable include: child’s age, child’s gender, if males are circumcised or not, child’s order in his family, father’s level of education, mother’s level of education, place of residence and family socioeconomic status. Methodology: A descriptive study was conducted on students of primary schools for both sexes, for the period from 19th. February 2014 through to 4th March 2014. A selected sample from two steps the first stage is to choose a school by a stratified- cluster sample, getting schools that have been selected (12) schools as representative for the schools of the Al Nasiriya, from the total (400) schools. The second step of selection of students by the disproportionately-stratified sample chosen from which (120) students from the Al Nasiriya city. Result(s): The results of the study indicate that most of the incidence occur with the age (12-14) years, and most likely with males rather than female. The study showed the presence of a statistically significant relationship between urinary tract infections and (viscourithral reflex; fever; abdominal and pelvic pain; back pain; chronic constipation and nausea & vomiting). The study also demonstrates the presence of a statistically significant relationship between urinary tract infections in the prepubertal children and between (dysuria; hematuria; urinary incontinence and pinworms; irritation of perineal area and wear tight clothes). Recommendation: The study recommends that the Ministry of Health has to apply a wide program or investigate large-scale survey throughout Iraq for the purpose of assessing the spread of urinary tract infections in primary schools. Also, the study recommends a special program to be conducted in conjunction with Ministry of Education to assess, and give children a primary care plan to cease the spread of urinary tract infection among them.